Dedicated dads: a study on the nesting behaviour of Spondyliosoma emarginatum (Telostei: Sparidae) - Faure, Beaulieu Nina (Department of Biological Sciences, 2021)
Fish display the most diverse parental care behaviours within the animal kingdom. These behaviours are important from evolutionary and conservation perspectives as parental care is critical for the development and survival of the young. This study used video monitoring to uncover the nesting behaviour of an endemic southern African species of the Sparidae family, Spondyliosoma emarginatum (steentjie). S. emarginatum has evolved a nesting strategy by which males create nests on the seafloor for females to lay their eggs in. The eggs are fertilised and guarded by the male until they hatch. This species is particularly interesting as it has evolved a life-history strategy unique to the Sparidae, a combination of protogyny (female to male sex change) and male parental care. A compound nesting site with over 50 nests was discovered in 9 to 14 m depth in False Bay, South Africa. A large diversity in nest size and habitat was uncovered. The first nest with eggs appeared on the 3rd of September and this number gradually increased to a maximum of 26 nests on the 3rd of October. Eggs took from seven to nine days to hatch. During nesting, males were affected by stochastic weather events in the form of south-easterly gales. Nesting sites are likely limited to sheltered bays along South Africa's mostly exposed coast, and the optimal depth is probably a tradeoff between storm exposure and temperature. Deeper nests are expected in the east where the water is warmer. Nests were filmed daily to reveal how male behaviour changes before egg deposition and during egg development. After egg deposition, males increased their time on the nest from 30 to 52 minutes per hour. Nest defence included the regular clearing of invertebrate invaders (brittle stars, hermit crabs, sea cucumbers, and sea stars), and chasing away other fish species (sand gobies, Roman, and hottentot) and neighbouring male steentjies. Energy intensive behaviours such as clearing the nest and fanning the eggs remained constant irrespective of egg presence. In addition, males do not feed when guarding eggs, which explains the drop in male condition during spring. The revelation of this nesting site is useful for conservation and fishery management as the nests and nesting males are vulnerable to both fishing and seabed disturbances. Spondyliosoma spp. fulfil the requirements of the size-advantage model of protogyny. Their short life-span, in particular, their even shorter egg-laying life-span, classifies this species as an opportunist. This strategy may explain its success and numerical dominance in a wide range of biogeographic zones. The nesting behaviours shares much in common with freshwater opportunistic fish species and set it apart from the bulk of the Sparidae.